Development and Priority Selection of Marketing Strategies for Pangas Catfish Skin Chips at Gatiga Snack MSMEs - Novriyanti, Eka; Sylvia, Teny; Sembiring, Noveliska Br (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2025)
Gatiga Snack MSMEs, a chip producer in South Lampung, faces tough competition and requires effective marketing strategies to grow. This study aims to develop and select strategies that can be implemented by Gatiga Snack using SWOT analysis and QSPM. Based on the SWOT analysis results, 18 recommended strategies were obtained. These strategies are then prioritized using QSPM analysis. There are three recommended strategy implementation periods. In the first period, six strategies were recommended that could be implemented. The highest TAS score among the strategies in the first period was forming a special marketing team for managing the Gatiga Snack MSME business (WO4), amounting to 7.296. In the second period, six strategies were also recommended that could be implemented. An intensive promotional strategy by creating a schedule of online and offline routine promotional activities (WO2) resulted in the highest TAS score of 7.141 in the second period. The third-period strategy consisted of six strategies with the highest TAS score of 7.031, namely building a brand image by making reviews or testimonials about the quality of Pangas Catfish Skin Chips’s Gatiga Snack so that new consumers would trust and be interested in buying (ST3).